2020
DOI: 10.3390/pr8040410
|View full text |Cite
|
Sign up to set email alerts
|

NMR Determination of Free Fatty Acids in Vegetable Oils

Abstract: The identification and quantification of free fatty acids (FFA) in edible and non-edible vegetable oils, including waste cooking oils, is a crucial index to assess their quality and drives their use in different application fields. NMR spectroscopy represents an alternative tool to conventional methods for the determination of FFA content, providing us with interesting advantages. Here the approaches reported in the literature based on 1H, 13C and 31P NMR are illustrated and compared, highlighting the pros and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 60 publications
4
43
0
2
Order By: Relevance
“…Chemically, in this study, five structures of Holothuria A (1), Holothuria B (2), palmitic acid (3), bis (2-ethylhexyl) phthalate (4), and 2-BTHF (5) were isolated for the first time from the sea cucumber H. scabra. Holothuria A (1) and B (2) are new diterpene glycosides [60,61], while the rest-(3) [62], (4) [63], and (5) [40][41][42]-are known structures. Regarding anti-Aβ's therapeutic ability, our results strongly indicated that diterpene glycosides including Holothuria A (1) and B (2) had no in vivo anti-Aβ toxic effect in delaying the paralysis of the treated worms.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically, in this study, five structures of Holothuria A (1), Holothuria B (2), palmitic acid (3), bis (2-ethylhexyl) phthalate (4), and 2-BTHF (5) were isolated for the first time from the sea cucumber H. scabra. Holothuria A (1) and B (2) are new diterpene glycosides [60,61], while the rest-(3) [62], (4) [63], and (5) [40][41][42]-are known structures. Regarding anti-Aβ's therapeutic ability, our results strongly indicated that diterpene glycosides including Holothuria A (1) and B (2) had no in vivo anti-Aβ toxic effect in delaying the paralysis of the treated worms.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was stirred (220 rpm) continuously at atmospheric pressure and 28 • C. Reaction progress was evaluated for 24, 48 and 74 h. Samples were collected, filtered and the solvent was evaporated. An aliquot of 20 mg of the crude material of the reaction was dissolved in deuterated chloroform and the resulting solution was analyzed by NMR [65][66][67][68][69] and GC-FID. Experiments were carried out in triplicate.…”
Section: Enzymatic Preparation Of Ethyl Estersmentioning
confidence: 99%
“…In the second step, the hydrolyzed oil was used to perform the esterification reactions using the same biocatalysts indicated above. A mixture of hydrolyzed monkfish liver oil (0.300 g; 1 mmol), biocatalyst (0.03 g, 10% w/w based on the weight of hydrolyzed monkfish liver oil) and ethanol (0.147 g; 3.2 mmol) were stirred (220 rpm) at 28 • C. The esterification reactions were conducted for 24, 48 or 72 h. The reaction products were analyzed by NMR [65][66][67][68][69] and GC-FID. All the experiments were carried out in triplicate.…”
Section: Two-step Synthesis: Hydrolysis and Esterification Reactionsmentioning
confidence: 99%
“…Se determina mediante la 14 titulación o valoración del aceite disuelto en alcohol con una solución estándar de KOH. El valor del IA refleja el contenido de AGL, producto de la hidrólisis (Di Pietro et al, 2020). El IA determinado en el biodiesel es importante para determinar el nivel de AGL o ácidos presentes, pues refleja la calidad del biodiesel, ya que si este índice es alto, incrementa los depósitos en el sistema de combustión e incrementan la potencialidad de corrosión del sistema.…”
Section: Calidad Del Aceite De Las Semillas De Piñónunclassified